ASSISTING THE IMPLEMENTATION OF THE LEAN WASTE SYSTEM THROUGH THE LOGISTICS SERVICE INDUSTRY - Kurniati , Ary; Pradana, Fxik Ardi; Pratama, Oktioza (IJOSMAS, 2021)
Business strategy is indispensable to company become more active and sensitive for future threats. For external factor, environmental uncertainty need to be considered for improving their strategy and from internal factor is performance. This research will discuss the linkage among business strategy with uncertainty and performance in the field of freight forwarder Indonesia and logistic by financial and non-financial. The required data are questionnaire survey and using the data from some companies to analyze with approach of porter strategy (Russell T. Westcott et al. n.d.), before testing analysis, factor score of questioner will be calculated first with regresion after that, ANOVA result will be checked whether linkaged or not. Methods: The data sources in this study used primary and secondary data, which were then tested for validity and reliability, then a linear regression test was carried out to find out whether the value was significant or influential, whether there was a correlation or not, and ANOVA results were produced to determine whether there was a relationship or not. The results of the research number of respondents in this study were 100 respondents. Most of the the relationship between business strategy and environmental uncertainty (0.000), business strategy and financial performance (0.000), the relationship between environmental uncertainty and financial performance (0.000) and environmental uncertainty and non-financial performance (0.013).so that it can be concluded that there is a the significance value obtained is below 0.05 so that it is said to be valid, has influence and Ho is rejected which shows that there is a relationship between each variable.